2015
DOI: 10.1111/pce.12558
|View full text |Cite
|
Sign up to set email alerts
|

Rapid responses of mesophyll conductance to changes of CO2 concentration, temperature and irradiance are affected by N supplements in rice

Abstract: Photosynthesis in C3 plants is significantly limited by mesophyll conductance (gm ), which can vary with leaf anatomical traits and nitrogen (N) supplements. Several studies have investigated the response of gm to N supplements; however, none examined the implications of N supplements on the response of gm to rapid environmental changes. Here we investigated the effect of N supplement on gm and the response of gm to change of CO2 , temperature and irradiance in rice. High N supplement (HN) increased mesophyll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 53 publications
6
139
0
1
Order By: Relevance
“…In this study, g m decreased in rice after the increase in the measurement temperature, but this decrease was not significant in wheat. In contrast, an increase in g m with measurement temperature was reported by von Caemmerer and Evans (2015) and supported by data from Xiong et al (2015) in rice. A recent reported showed a decline in g m as leaves aged from fully expanded to senescing (Barbour et al, 2016), supporting that the above discrepancies reflect the importance of the experimental conditions and leaf age.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, g m decreased in rice after the increase in the measurement temperature, but this decrease was not significant in wheat. In contrast, an increase in g m with measurement temperature was reported by von Caemmerer and Evans (2015) and supported by data from Xiong et al (2015) in rice. A recent reported showed a decline in g m as leaves aged from fully expanded to senescing (Barbour et al, 2016), supporting that the above discrepancies reflect the importance of the experimental conditions and leaf age.…”
Section: Discussionsupporting
confidence: 80%
“…The net CO 2 assimilation rate ( A N ) and the stomatal conductance ( g s ) were measured at mid-morning at a leaf temperature of 25°C, saturating PPFD of 1500 μmol m -2 s -1 (provided by the light source of the Li-6400-40, with 10% blue light), a CO 2 concentration in the leaf chamber ( C a ) of 400 μmol CO 2 mol -1 air and a relative humidity between 40 and 50%. A PPFD of 1500 μmol m -2 s -1 was considered to provide photosynthesis saturation for the glasshouse grown plants (Makino et al, 1994; Grassi and Magnani, 2005; Centritto et al, 2009; Ghannoum, 2009; Tazoe et al, 2009; Zhu et al, 2012; Xiong et al, 2015). The leaf dark respiration rate ( R dark ) was determined at pre-dawn (i.e., shortly before the start of the light period) at a C a of 400 μmol CO 2 mol -1 air.…”
Section: Methodsmentioning
confidence: 99%
“…In the last 10–15 years, considerable efforts have been focused on the chloroplast features that determine g m . These have shown that there is a tight relationship between the area of chloroplast surface exposed to intercellular airspaces ( S c ) and g m 22, 2426 . In mesophyll cells, chloroplasts are usually located next to the cytoplasmic membrane adjacent to intercellular air spaces, which was suggested to decrease resistance to CO 2 diffusion 25 .…”
Section: Introductionmentioning
confidence: 99%